RANK, RANKL and osteoprotegerin in arthritic bone loss - Bezerra,M.C. (2005)
Rheumatoid arthritis is characterized by the presence of inflammatory synovitis and destruction of joint cartilage and bone. Tissue proteinases released by synovia, chondrocytes and pannus can cause cartilage destruction and cytokine-activated osteoclasts have been implicated in bone erosions. Rheumatoid arthritis synovial tissues produce a variety of cytokines and growth factors that induce monocyte differentiation to osteoclasts and their proliferation, activation and longer survival in tissues. More recently, a major role in bone erosion has been attributed to the receptor activator of nuclear factor kappa B ligand (RANKL) released by activated lymphocytes and osteoblasts. In fact, osteoclasts are markedly activated after RANKL binding to the cognate RANK expressed on the surface of these cells. RANKL expression can be upregulated by bone-resorbing factors such as glucocorticoids, vitamin D3, interleukin 1 (IL-1), IL-6, IL-11, IL-17, tumor necrosis factor-alpha, prostaglandin E2, or parathyroid hormone-related peptide. Supporting this idea, inhibition of RANKL by osteoprotegerin, a natural soluble RANKL receptor, prevents bone loss in experimental models. Tumor growth factor-ß released from bone during active bone resorption has been suggested as one feedback mechanism for upregulating osteoprotegerin and estrogen can increase its production on osteoblasts. Modulation of these systems provides the opportunity to inhibit bone loss and deformity in chronic arthritis.